THE EFFECTIVENESS OF THE IMPLEMENTATION OF TTW STRATEGY IN MATHEMATICS LEARNING BASED ON THE STUDENTS’ LEARNING STYLES - Patmawati; Abdul Rahman; Asdar (P3M STMIK Profesional Makassar, 2016)
The research aims at discovering the effectiveness level of the Think Talk Write (TTW) Strategy in mathematics learning based on the students’ learning styles at SMPS PPM Rahmatul Asri Enrekang. This researchis pre-experimental design with one group pretest-posttest design. The population in this research was all female students of class VIII at SMPS PPM Rahmatul Asri Enrekang which consisted of 3 classes and the samples of this research were class VIIIE with 20 persons and class VIIIF with 24 persons which had the same treatment, so the sample in this research counted as one group. The sampling technique was conducted by employing stratified cluster random sampling. The data collected consisted of the students’ learning outcomes, the students’ response data, and the learning implementation data. The results of the research reveal that (1) teacher’s activities in presenting the learning process with the implementation of TTW strategy is in good category, (2) the studens’ learning outcomes after the implementation of TTW strategy is better then the student’s learning outcomes before TTW strategy is implemented, (3) the students’ response whether visual, auditorial, and kinestetic style toward the lesson plan is in positive category, (4) students’ activities in learning process with TTW strategy implementation is in good category. The result of inferential analysis by using One Way Anova test shows that the TTW strategy implementation is effective in Mathematics learning, especially in cube and rectangle material.